Beyond medicine : why European social democracies enjoy better health outcomes than the United States - Dutton, Paul V. (The culture and politics of health care work, 2021)
In 'Beyond Medicine', Paul V. Dutton provides a penetrating historical analysis of why countless studies show that Americans are far less healthy than their European counterparts. Dutton argues that Europeans are healthier than Americans because beginning in the late nineteenth century European nations began construction of health systems that focused not only on medical care but the broad social determinants of health: where and how we live, work, play, and age. European leaders also created social safety nets that became integral to national economic policy. In contrast, US leaders often viewed investments to improve the social determinants of health and safety-net programs as a competing priority to economic growth. 'Beyond Medicine' compares the US to three European social democracies - France, Germany, and Sweden.